Target-controlled infusion vs. manually controlled infusion of propofol with alfentanil for bidirectional endoscopy: a randomized controlled trial - Chiang, Min-Hsien; Wu, Shao-Chun; You, Chia-Hsun; Wu, Keng-Liang; Chiu, Yi-Chun; Ma, Chao-Wei; Kao, Chin-Wei; Lin, Kun-Chen; Chen, Kuan-Hung; Wang, Peng-Chih; Chou, An-Kuo (Endoscopy, 2013)
Background and study aims: The best anesthesia methods for analgesia and sedation during gastrointestinal endoscopy are still debated. The aim of this study was to compare the recovery time, clinical presentations, and satisfaction between target-controlled infusion (TCI) and manually controlled infusion (MCI) in same-day bidirectional endoscopy (esophagogastroduodenoscopy followed by colonoscopy).Patients and methods: A total of 220 patients with American Society of Anesthesiology physical status 1 or 2 were enrolled and randomized into the TCI or MCI groups. The clinical presentations, vasoactive drug demand, propofol consumption, and adverse events were recorded for both groups peri-procedurally. The concentrations of propofol in the plasma (Cp) and at the site of drug effect (Ce) by computerized simulation were also monitored in both groups. Finally, the satisfaction of patients, endoscopists, and nurse anesthetists was assessed by questionnaire after the examinations.Results: Compared with the MCI group, the TCI group had a faster recovery time (17.91 ± 7.72 minutes vs. 14.58 ± 8.55 minutes; P = 0.002), less moderate hypotension (7.37 ± 15.46 % vs. 1.82 ± 5.15 %; P < 0.001), and shorter period of bradypnea (13.81 ± 15.92 % vs. 9.18 ± 12.00 %; P = 0.013). In addition, the TCI group reduced the relative risk of moderate desaturation by 50 % compared with the MCI group (30.9 % vs. 15.5 %; 95 % confidence interval 1.191 – 3.360; P = 0.007).Conclusions: The study demonstrated that TCI of propofol combined with alfentanil was associated with a faster recovery time, and better hemodynamic and respiratory stability than MCI in same-day bidirectional endoscopy.Clinical trial registration: CGMH IRB Identifier 97-0969B